Data collection with farmers in bean pest and disease management using the Open Data Kit - Arinaitwe, Warren; Aritua, Valentine; Muthoni Andriatsitohaina, Rachel (2015)
Data collection with ODK part of a 3 –year project aimed at Supporting investments for upscaling of grain legumes in western Kenya through assessing and modeling the threat of biotic stressors.